To breve fra N. F. S. Grundtvig. Udgivet og kommenteret - Pedersen, Kim Arne (Grundtvig-Studier, 2007)
To breve fra N. F. S. Grundtvig [Two letters from N. F. S. Grundtvig] By Kim Arne Pedersen Two letters written by N. F. S. Grundtvig from, respectively, Lisbeth and Povl Kiilerich’s and Steffen Lauge’s private collections are here published in transcription with an explanatory commentary. The first letter has belonged in Lisbeth Kiilerich’s family - in the possession, that is, of the Hvidt family - for several generations. In the letter, Grundtvig refers to a theological discussion he has had with its recipient, the speculative and Daub-influenced theologian V. H. Rothe (1777-1857). Grundtvig expresses himself forcibly but is not looking for hostilities. In the second letter, he tells his sister-in-law Jane Mathia Blicher (1792-1853) of his visit to Norway in 1851. The letter conveys a good and lively picture of the journey and the homage paid to Grundtvig there.